Is the whitening effect of charcoal-based dentifrices related to their abrasive potential or the ability of charcoal to adsorb dyes? - da Silva, Douglas Ferreira [UNESP]; Figueiredo, Fernanda Consiglio [UNESP]; Scaramucci, Taís; Mailart, Mariane Cintra [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Borges, Alessandra Buhler [UNESP] (Elsevier, 2024)
Objectives: To evaluate if tooth color alteration of activated charcoal-based dentifrices may be attributed to the dye adsorption potential of charcoal (chemical action - C - slurry only) or to the association of dye adsorption with abrasion (chemo-mechanical action - CM- slurry/toothbrushing). Potential adverse effects in surface roughness, gloss, and wear were also assessed. Methods: Bovine enamel/dentin specimens were randomly allocated into the groups according to treatments and test model (n = 15): deionized water (negative control- NC); Colgate Maximum Anticaries Protection (conventional toothpaste- positive control- PC); Colgate Luminous White Activated Charcoal (LW); Oral-B 3D White Therapy Charcoal (WT); Curaprox Black is White (BW); Dermavita Whitemax (Activated charcoal powder- WP). Specimens were exposed to the C or CM models, in 28-day staining-treatment cycling. Color change (ΔE00), whiteness index (ΔWID), percentage of alteration of surface roughness (%Raalt), and gloss (%GUalt) were calculated. Additional specimens (n = 9) were indented with a Knoop diamond and subjected to 100,000 abrasion cycles. Enamel wear was determined by calculating the decrease in indentations geometry. Data were analyzed by ANOVA/Tukey tests (α = 0.05). Results: The CM-model produced lower color change (staining) than C (p = 0.0001). PC, LW, WT, BW, and WP showed similar color results for both models, differing from NC (p < 0.05).%Ra and%GU did not differ among the C-model groups (p > 0.05) and WP exhibited the highest variation (%Ra and%GU) under CM-model. Enamel wear values were lowest in the NC and PC groups, intermediate for LW, WT, BW, and highest for the WP (p < 0.05). Conclusion: Activated charcoal-based dentifrices have a similar ability to minimize tooth staining as the conventional toothpaste, with increased enamel wear potential in the long term (after 100,000 cycles). The activated charcoal powder damaged the enamel surface, showing a higher deleterious effect on enamel roughness, gloss, and wear. Clinical significance: Dentifrices containing activated charcoal do not provide superior results to minimize tooth staining compared to conventional toothpaste. Charcoal powder should be used with caution because it promotes higher superficial alterations on the enamel surface.
Keywords: Activated charcoal; Color; Dental enamel; Dentifrices; Tooth abrasion